2022
DOI: 10.18502/ajmb.v14i1.8174
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activities of Green Tea by Up-regulation of miR-181a Expression in LNCaP Cells Using 3D Cell Culture Model

Abstract: Background: Prostate Cancer (PCa) is the major reason for the high mortality rates among men worldwide. In fact, current therapeutic approaches are not successful. It appears that discovering more effective methods considering several parameters such as availability, low cost, and no toxicity to normal cells is one of the biggest challenges for interested researchers. Green tea (extracted from the plant Camellia sinensis) with high level of polyphenolic compounds and as the most globally consumed beverage has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Additionally, changes in the adhesion behavior of treated cells consistent with a reduction in the formation of colonies were also reported [ 41 ]. GTE’s ability to reduce spheroid growth has been demonstrated in 3D cultures of 4T1 murine mammary carcinoma cells [ 42 ] and prostate LNCaP [ 43 ]. We also demonstrated that spheroid formation was impaired in a GTE-containing medium, leading to irregular aggregates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, changes in the adhesion behavior of treated cells consistent with a reduction in the formation of colonies were also reported [ 41 ]. GTE’s ability to reduce spheroid growth has been demonstrated in 3D cultures of 4T1 murine mammary carcinoma cells [ 42 ] and prostate LNCaP [ 43 ]. We also demonstrated that spheroid formation was impaired in a GTE-containing medium, leading to irregular aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…The GT mechanisms of action on MMPs can also be seen through the control of their translation, and in this field the modulation of microRNAs may offer a therapeutic alternative. The exposure of LNCaP prostate cancer spheroids to 100–1000 µg/mL of GTE for 48 h led to an increase in miR-181a expression [ 43 ]. MiR-181a are known to inhibit migration and angiogenesis through the regulation of MMP-14 in SK-3 breast cancer cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is one of the most investigated natural compounds in this context, and it has demonstrated anti-tumor effects on many tumor types, including prostate [ 113 , 176 , 177 ]. However, the search for new natural inhibitors continues, as many are being tested on PC spheroids, such as flavokawain A [ 178 ], brachydin A [ 109 ], green tea extract [ 110 ], rosmarinic acid [ 116 ], or grape seed extract [ 115 ].…”
Section: Standard and Novel Therapies Used In 3d Models Of Pcmentioning
confidence: 99%
“…The major polyphenolic constituent of Poly E, EGCG, has been reported to regulate several key cellular signaling pathways [12][13][14], proinflammatory factors [15,16], and apoptosis [17,18]. It has been suggested that EGCG is less effective alone in its beneficial health properties than it is in conjunction with the other polyphenolic compounds naturally found in green tea, and in Poly E [19].…”
Section: Introductionmentioning
confidence: 99%